2019
DOI: 10.1101/812123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absolute quantification of transcription factors reveals principles of gene regulation in erythropoiesis

Abstract: SummaryDynamic cellular processes such as differentiation are driven by changes in the abundances of transcription factors (TFs). Yet, despite years of studies we still do not know the protein copy number of TFs in the nucleus. Here, by determining the absolute abundances of 103 TFs and co-factors during the course of human erythropoiesis, we provide a dynamic and quantitative scale for TFs in the nucleus. Furthermore, we establish the first Gene Regulatory Network of cell fate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 82 publications
0
34
0
Order By: Relevance
“…We have previously shown that TFII-I interacts with HDAC3 and functions as a repressor of adult β-globin gene expression in erythroleukemia cell lines ( Crusselle-Davis et al, 2006 ). Gillespie et al (2020) recently performed a proteomic study in primary differentiating erythroid cells. The relative expression data for TFII-I demonstrate that it is up-regulated during differentiation of erythroid cells and declines in expression concomitant with the up-regulation of adult β-globin gene expression ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that TFII-I interacts with HDAC3 and functions as a repressor of adult β-globin gene expression in erythroleukemia cell lines ( Crusselle-Davis et al, 2006 ). Gillespie et al (2020) recently performed a proteomic study in primary differentiating erythroid cells. The relative expression data for TFII-I demonstrate that it is up-regulated during differentiation of erythroid cells and declines in expression concomitant with the up-regulation of adult β-globin gene expression ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…(A) Relative protein expression levels for TFII-I, β-globin, and TBP during differentiation of erythroid cells. Data were extracted from a proteomic study by Gillespie et al (2020) . MPP, multiple progenitor population; CMP, common myeloid progenitors; MEP, myeloid erythroid progenitors; CFU-E, colony forming unite-erythroid; ProEB, proerythroblast; Baso EB, basophilic erythroblast.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of clustered homotypic TF binding sites associated with gene control is the binding of ZFP64 to the MLL gene promoter, activating the expression of the chromatin regulator MLL, although in this case ZFP64 shows a limited set of additional direct target genes 32 . CHD4 is an especially abundant nuclear protein in erythroid precursors 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in principle DIA should offer a more comprehensive analysis of peptides and as a consequence could be more suitable for MS analysis of chromatin (domains). Finally, when specific chromatin factors or TFs are subject of study, selective reaction monitoring (SRM) can be used to specifically measure the abundance of tens to hundreds of pre-selected proteins over a wide range of abundances (72). Further research is required to optimise and implement these mass spectrometry data acquisition methods for low input chromatin proteomics studies, but important lessons can perhaps be learned from the emerging field of single-cell proteomics, which deals with extremely low amount of input sample (73).…”
Section: The Biochemical Challenges and Opportunitiesmentioning
confidence: 99%